Autogenic avulsion, channelization and backfilling dynamics of debris‐flow fans. Issue 6 (25th May 2016) - de Haas, Tjalling; van den Berg, Wilco; Braat, Lisanne; Kleinhans, Maarten G.
Abstract: Alluvial fans develop their semi‐conical shape by quasi‐cyclic avulsions of their geomorphologically active sector from a fixed fan apex. On debris‐flow fans, these quasi‐cyclic avulsions are poorly understood, partly because physical scale experiments on the formation of fans have been limited largely to turbidite and fluvial fans and deltas. In this study, debris‐flow fans were experimentally created under constant extrinsic forcing, and autogenic sequences of backfilling, avulsion and channelization were observed. Backfilling, avulsion and channelization were gradual processes that required multiple successive debris‐flow events. Debris flows avulsed along preferential flow paths given by the balance between steepest descent and flow inertia. In the channelization phase, debris flows became progressively longer and narrower because momentum increasingly focused on the flow front as flow narrowed, resulting in longer run‐out and deeper channels. Backfilling commenced when debris flows reached their maximum possible length and channel depth, as defined by channel slope and debris‐flow volume and composition, after which they progressively shortened and widened until the entire channel was filled and avulsion was initiated. The terminus of deposition moved upstream because the frontal lobe deposits of previous debris flows created a low‐gradient zone forcing deposition. Consequently, the next debris flow was shorter which led to more in‐channel sedimentation, causing more overbank flow in the next debris flow and resulting in reduced momentum to the flow front and shorter runout. This topographic feedback is similar to the interaction between flow and mouth bars forcing backfilling and transitions from channelized to sheet flow in turbidite and fluvial fans and deltas. Debris‐flow avulsion cycles are governed by the same large‐scale topographic compensation that drives avulsion cycles on fluvial and turbidite fans, although the detailed processes are unique to debris‐flow fans. This novel result provides a basis for modelling of debris‐flow fans with applications in hazards and stratigraphy.